The impact Of high-intensity interval training On functioning And health-related quality Of life In post-stroke patients: A systematic review With meta-analysis. (June 2022) - Anjos, Jorge Motta; Neto, Mansueto Gomes; dos Santos, Franciele Silva; Almeida, Katna de Oliveira; Bocchi, Edimar Alcides; Lima Bitar, Yasmin de Souza; Duraes, Andre Rodrigues
Objective: To examine the effects of high-intensity interval training on the functioning and health-related quality of life of post-stroke patients. Methods: We searched the following electronic databases: MEDLINE/Pubmed, Cochrane Central Register of Controlled Trials, PEDro database, and Scielo up to January 2022 for randomized controlled trials that investigated the effects of high-intensity interval training in post-stroke patients. Two reviewers selected the studies independently. Study quality was evaluated using the PEDro scale. The mean difference (MD), standard mean difference (SMD), and 95% confidence intervals (CIs) were calculated. Results: Nine studies met the study criteria (375 patients). The age of the participants ranged from 55.8 to 72.1 years. The studies included patients within 2 weeks of stroke onset to patients longer than 1 month of stroke. High-intensity interval training resulted in improvement in cardiorespiratory fitness (peak oxygen uptake) MD (3.8 mL/kg/min, 95% CI: 2.62, 5.01, n = 91), balance MD 5.7 (95% CI: 3.50, 7.91; N = 64), and gait speed SMD (0.2 m/s; 95% CI: 0.05, 0.27; N = 100) compared with continuous aerobic training. The health-related quality of life did not differ between the groups. Compared to usual care, high-intensity interval training improved the cardiorespiratory fitness SMD (0.5 95% CI: 0.14, 0.81, n = 239). No serious adverse events were observed. Conclusions: The findings of this systematic review show that high-intensity interval training was more efficient than continuous aerobic training to gain cardiorespiratory fitness, balance and gait speed in post-stroke patients. In addition, compared to usual care, high-intensity interval training improved cardiorespiratory fitness.